Multicenter randomized controlled trial of bifrontal, bitemporal, and right unilateral electroconvulsive therapy in major depressive disorder. Issue 10 (23rd July 2019) - Su, Liang; Jia, Yuping; Liang, Shiqiao; Shi, Shenxun; Mellor, David; Xu, Yifeng
Abstract : Aim: Electroconvulsive therapy (ECT) has been shown to be the most effective and rapid treatment for severe depression. Electrode placement is one of the most important factors that affect ECT's efficacy and side‐effects profile. Bifrontal, bitemporal, and unilateral are the three most used electrode placements. Very few studies have directly compared the efficacy and cognitive side‐effects of the three placements. The aim of this study was to compare the efficacy and cognitive side‐effects associated with bifrontal, bitemporal, and unilateral electrode placements. Methods: This multicenter randomized, blinded, controlled trial included 40 patients in each of the three groups. Most of the patients (94.8%) completed six ECT treatments. We used mixed‐model analyses to compare differences in 17‐item Hamilton Depression Rating Scale (HAMD‐17) and Clinical Global Impression (CGI) scores among the three groups and the five times series (baseline, Week 1, Week 2, Week 3, and Week 4). The cognitive outcome was Mini‐Mental State Examination (MMSE) score. Results: HAMD‐17 and CGI scores did not differ significantly across the groups (HAMD‐17 scores: z = −1.13, P = 0.259; CGI scores: z = −0.35, P = 0.729). MMSE scores at pre‐ and post‐ECT were similar across the three groups ( F = 2.06, P = 0.133). However, subgroup analysis using paired t ‐tests showed that MMSE scores improved in the right unilateral and bifrontal groups ( t = 2.745, P = 0.0098; t = 2.464, P = 0.0204), but did not change in the bitemporal group ( t = 1.188, P = 0.2461). Conclusion: The efficacy of right unilateral and bifrontal ECT placement was similar to that of bitemporal ECT. The physical side‐effects were also similar across the three groups. Right unilateral and bifrontal ECT placement were associated with improved cognitive outcomes, but bitemporal ECT placement was not.